Peranan Pengawas Pada Guru Pendidikan Agama Kristen Dalam Membentuk Karakter Siswa - Nababan, Mayarita (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
Seeing the current phenomenon, people's attitudes and behavior tend to ignore noble values, resulting in a character crisis. Cases such as drug abuse, bullying, and brawls show a decline in morals, mentality, and ethics, especially in the younger generation of the nation's successors, so character education is something that schools, including Christian religious education teachers, need to pay attention to. This study aims to determine the extent of the role of PAK teachers in character education and to determine the application of character education. This research was conducted on the awareness of the importance of the role of Christian Religious Education teachers in developing the character of Christ. This study uses a qualitative method because this method uses data in the form of words or narratives. The data was taken through interview techniques to respondents who were judged to be able to provide accurate information as needed in this study. The findings of the data obtained from this study are first, character education is applied in all subjects in school and even extracurricular. Second, the role of schools in developing character education has been carried out in accordance with the vision and mission, motto and in accordance with the character of Christ, which includes loving, forgiving, caring, humble, patient, sincere, willing to share, obedient, and mutual respect. Third, the role of the PAK teacher is very important in the application of character education in accordance with the character of Christ. Teachers are expected to carry out their role in educating students according to and leading to the character of Christ. This role is carried out by acting and imitating attitudes not only as a teacher but also as a friend, motivator, and agent of change for his students